Optimization And Simulation Of Solar PV Based Hybrid System Using Homer Software - Sunaina, Harpreet Kaur Channi, Surbhi Gupta (International Journal of Advanced Science and Technology, 2020)
This paper presents a techno-economic analysis of solar hybrid energy system for the village of Patyari Kaltan, located in Jammu, India, considering the actual load and other meteorological data. Initially the energy system is built by keeping the load pattern in mind and also the existence of the renewable sources in that particular area. The hybrid system is specifically intended to meet the load demand in varying times by combining various renewable power sources such as wind turbines, solar panels along with battery. The simulation software used in this research is HOMER and simulation result shows that the best combination system for the electricity generation is solar-Battery hybrid system having NPC and price of electricity is $9009.43 and $0.6369/kWh. In this research paper the sensitivity analysis is also done to examine the future performance of the system.